2015
DOI: 10.3389/fmicb.2015.00898
|View full text |Cite
|
Sign up to set email alerts
|

The effect of human settlement on the abundance and community structure of ammonia oxidizers in tropical stream sediments

Abstract: Ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) are a diverse and functionally important group in the nitrogen cycle. Nevertheless, AOA and AOB communities driving this process remain uncharacterized in tropical freshwater sediment. Here, the effect of human settlement on the AOA and AOB diversity and abundance have been assessed by phylogenetic and quantitative PCR analyses, using archaeal and bacterial amoA and 16S rRNA genes. Overall, each environment contained specific clades of amoA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…When unclassified Nitrosomonadacaea was excluded, the abundance of Nitrosomonas was higher than that of Nitrosospira in wastewater‐ influenced sediments. These two AOB clades are physiologically distinct, Nitrosospira ‐like AOB being more abundant in low ammonium conditions, while Nitrosomonas ‐like AOB have been suggested to be adapted to grow in ammonium‐rich environments, for example, in eutrophic sediments (Peng et al ., ; Reis et al ., ). Altogether, these results indicate that although wastewater can promote the abundance of certain AOB groups ( Nitrosomonas ) through habitat modification and migration from WWTP, other groups can still coexist.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…When unclassified Nitrosomonadacaea was excluded, the abundance of Nitrosomonas was higher than that of Nitrosospira in wastewater‐ influenced sediments. These two AOB clades are physiologically distinct, Nitrosospira ‐like AOB being more abundant in low ammonium conditions, while Nitrosomonas ‐like AOB have been suggested to be adapted to grow in ammonium‐rich environments, for example, in eutrophic sediments (Peng et al ., ; Reis et al ., ). Altogether, these results indicate that although wastewater can promote the abundance of certain AOB groups ( Nitrosomonas ) through habitat modification and migration from WWTP, other groups can still coexist.…”
Section: Discussionmentioning
confidence: 97%
“…Although a proportion of AOB was suggested to originate from wastewater treatment plant (see also Mußmann et al ., ; Pan et al ., ), the dynamics between AOA and AOB abundance were mainly directly driven by wastewater itself. Previous studies have reported that AOA thrive under stable and oligotrophic conditions, while dynamic and nitrogen‐rich conditions favour AOB in aquatic environments (Laanbroek et al ., ; Bollman et al ., ; Reis et al ., ). From an ecological perspective, these results indicate that there might be some differences in the stability of AOA and AOB communities, seen as different resistance to changes in environmental conditions.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The distribution of sediment ammonia-oxidizing archaeal and bacterial populations has been investigated in a variety of freshwater ecosystems, such as river (Reis et al 2015;Sonthiphand et al 2013;Sun et al 2013;Xie et al 2014), reservoir , lake (Bollmann et al 2014;Hou et al 2013;Liu et al 2015;Mukherjee et al 2016;Zhao et al 2013Zhao et al , 2014, wetland (Liu et al 2014a;Wang et al 2013;Yang et al 2014), and pond (Lu et al 2015), yet the relative importance of AOA and AOB to nitrification process in freshwater sediments remains under debate. Several previous studies indicated that AOA amoA gene abundance was usually greater than AOB in lake sediments (Herrmann et al 2009;Hou et al 2013;Zhao et al 2014), while the numerical dominance of AOB over AOA amoA gene abundance was observed in sediments of many freshwater lakes on the Yunnan Plateau (Liu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…and Methanosarcina sp., suggesting that both acetate and other compounds such as methanol and methylamines were being used as substrate for methanogenesis. A subsequent study by the same group [71] investigated the effect of human settlement in mining areas on ammonia oxidizing microorganisms present in these kinds of sediments. Archaeal amoA genes were detected in both impacted and nonimpacted sediments, but most abundantly in the nonimpacted sediment.…”
Section: Archaea In Marine and Freshwater Sedimentsmentioning
confidence: 99%